How Can Small States Like Iceland Work Effectively With International Financial Institutions? - Hilmar Þór Hilmarsson (The University of Akureyri, 2010)
Conducting a constructive relationship with international financial institutions (IFIs) can be a challenge for small states like Iceland. Iceland is a member of the World Bank Group and the European Bank for Reconstruction and Development, but not a member of the regional development banks, i.e.: the Asian Development Bank, the Inter-American Development Bank and the African Development Bank. IFIs work both with the governments of emerging market economies in formulating and supporting policy reforms as well as with the private sector as private sector lead projects can help boost economic reconstruction in emerging markets. But can small states work effectively in partnership with IFIs? This article will discuss the challenges faced by small states in working with IFIs both when supporting government reforms in emerging market economies as well as when promoting private sector activities and investment in those economies.